PENGARUH MOTIVASI KERJA DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. ALASKA MANDIRI CEMERLANG DI MAKASSAR - Hasyim Hasyim (Jurnal Bisnis dan Kewirausahaan, 2018)
This study aims: 1) to analyze the influence of work motivation on employee job satisfaction at PT. Alaska Mandiri Cemerlang in Makassar, 2) to analyze the influence of career development on employee job satisfaction at PT. Alaska Mandiri Cemerlang in Makassar. In this study used multiple regression analysis method. The research data used were obtained from interview, documentation and questionnaire. The results of this study indicate that: 1) based on the results of multiple regression tests, the effect of work motivation variables have a positive and significant impact on employee job satisfaction at PT. Alaska Mandiri Cemerlang in Makassar. This means that the better the provision of motivation, the higher the employee satisfaction of PT. Alaska Mandiri Cemerlang in Makassar. Vice versa, if motivation is not done then will cause employee dissatisfaction, and 2) based on result of multiple regression test, influence of career development variable have positive and significant effect to job satisfaction of employees at PT. Alaska Mandiri Cemerlang in Makassar. This means that the higher the career development the higher the employee work satisfaction of PT. Alaska Mandiri Cemerlang in Makassar. Vice versa, if career development is not done then will cause employee dissatisfaction.